Amidinato germylene-zinc complexes: synthesis, bonding, and reactivity - Yadav, Sandeep; Kumar, Rohit; Raj, K. Vipin; Yadav, Prashant; Vanka, Kumar; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
Despite the explosive growth of germylene compounds as ligands in transition metal complexes, there is a modicum of precedence for the germylene zinc complexes. In this work, the synthesis and characterization of new germylene zinc complexes [PhC(NtBu)(2)Ge{N(SiMe3)(2)}-> ZnX2](2)(X= Br (2) and I (3)) supported by (benz)-amidinato germylene ligands are reported. The solid-state structures of2and3have been validated by single-crystal X-ray diffraction studies, which revealed the dimeric nature of the complexes, with distorted tetrahedral geometries around the Ge and Zn center. DFT calculations reveal that the Ge-Zn bonds in2and3are dative in nature. The reaction of2with elemental sulfur resulted in the first structurally characterized germathione stabilized ZnBr(2)complexes PhC(NtBu)(2)Ge(=S){N(SiMe3)(2)}-> ZnBr2(5). Therefore, the Ge=S in5is in-between Ge-S single and Ge=S double bond length, owing to the coordination of a sulfur lone pair of electrons to ZnBr2.
Keywords: DFT; Germathione; Germylene; X-ray Structure; zinc